Micro Distribution of Plants in an Abandoned Salt Pit at Pachpadra Salt Basin - Rajpurohit, K S; Charan, A K; Sen, D N (Annals of Arid Zone, 2016)
The phytogeographical demarcation of a phygiographic microunit such as the one in Pachpadra salt basin, has been made here. This study illustrates as to how plant species are distributed according to the fluctuations in the salinity in water as well as in the soil.